Behavioral avoidance of experiences that could increase dissatisfaction related to body image - Santos Morocho, José (2021)
Adolescence, could be influenced by stereotypes of the slim, slender figure, which would mean a risk factor for the appearance and maintenance of avoidance behaviors towards the body The objective: was to evaluate avoidance behavior due to body image in a sample of ecuadorian adolescents. Methodology: analytical study, included 348 adolescents (12-19 years old), by means of probabilistic sampling. The Body Image Avoidance Questionnaire BIAQ was applied. Results: Women represented (58.33%). Sex, age and SCI, p> .05; (M = 13.68; SD = 1.71) (SCI) 48.57% (SD = 22.11) (middle social class). Avoidance behavior: clothing 53.74%; social activity 54.31%; dietary restriction 54.89%; grooming and weighing 50.28% Discussion: Behavioral avoidance of experiences may increase distress or dissatisfaction related to body image. Conclusion: The BIAQ - Spanish, evaluates avoidance behavior in adolescents.